Evaluating the effects of Thuja occidentalis extracts in reducing oral ulcer types - Jiyad, et.al, Jameel Hadi (Al-Qadisiyah Journal of Pure Science, 2017)
The oral ulcers are well-known diseases that effect peoples of different ages in Iraqi society . This study came to find a possible method to treat oral ulcers and to reduce the associated pains . These ulcers can occur in any part of the buccal cavity , and their causes include viruses , bacteria , fungi and other microorganisms . for these reasons , the plant Thuja occidentalis (Cupressaceae Family) was selected as an agent with reduction and growth inhibitor potentials for the causative agents of oral ulcers . The areas of these ulcers ranged from few squared millimeters to 10 squared millimeters or greater . Accordingly , a search was made for a drug that can reduce the causative agent of these diseases , and the choice was made for Thuja occidentalis because of the plant richness in flavonoids , glycosides , organic acids and some vegetable dyes . The plant was aqueously extracted (cold and hot extraction) , as well as using 70% ethanol . The results demonstrated that aqueous (cold and hot) and methanol extracts at a concentration of 2.0% were significantly effective (P<= 0.001) in reducing pains and recovering the oral ulcered areas of most of the investigated human groups , and the recovering percentage reached 80 , 79 , and 71 %, respectively of oral ulcers (10.1 ± 3.6 mm² ) withen 48 ± 6 hours .